Investigation of Dynamic, Mechanical, and Thermal Properties of Calotropis procera Particle-Reinforced PLA Biocomposites - K. Yoganandam; Vigneshwaran Shanmugam; A. Vasudevan; D. Vinodh; N. Nagaprasad; Balasubramaniam Stalin; Alagar Karthick; Chandrabhanu Malla; Murugesan Bharani (Advances in Materials Science and Engineering)
The thermal behavior of the biodegradable Calotropis procera (CP) particle-reinforced polylactic acid (PLA) biocomposites was investigated. The injection molding process was used to make the composites, and the CP particle weight percentage was varied during the process (0%, 5%, 10%, 15%, and 20%). The melt flow index, heat deflection temperature, Vicat softening point, and the thermal properties of the composites were determined using dynamic mechanical testing. The results were analyzed and compared to the thermal properties of the neat PLA. The results revealed the increase in thermal stability of the PLA due to the addition of CP particles. The CP particles aided in the restriction of polymer mobility, which elevated the glass transition temperature of the composite. Incorporating CP particles in the PLA can increase the PLA/CP composite utilization in heat dissipation applications.